VIOLATION OF MAXIM IN AMERICAN TV SHOW : JIMMY KIMMEL LIVE! - CHIRISTO KOPONG KOLIN, CLEMENTINO (LANGUAGE HORIZON, 2019)
Key words: Maxim, Violation of Maxim, Illocutionary function, Talk Show As social beings, human need to communicate in order to build socialitation itself. Human communicate using language which has a function as communication media and communication itself has general meaning as ordering or delivering information from one to another In social life, communication appears in term of conversation, while conversation itself can be explained as a kind of communication among two people or more in order to share an idea, opinion, information, and feeling. But sometimes there are misscommunication and akwardness happen in comunication especially in conversation which cause improper communication. Those akwardness and misscomunication happen because one of the speaker does a violation. The violation itself often founded in formal or informal conversation which not many people realized that it can cause improper and not informative communication. In terms of Linguistic, the violation which happens in conversation is a part of pragmatic study especially in cooperative violation maxim. Grice (1975:45-47) stated that a good conversation may happen if a speaker uses a cooperative maxim in a right way. Regarding to those communication problem which caused by violation in conversation the researcher choose one of American talk show Jimmy Kimmel Live! which include a guests that did not realized that they flouted the maxim while doing communication in formal conversation as a research topic. The aim of this research is to find out what are the types of maxim that flouted by the guest and the reasons behind the violation itself. . This research uses qualitative approach to answer the research questions. Qualitative approach is chosen as the methodology to analyse the data findings because it is the most suitable method to answer the research questions of the study. based on the data, it can be stated that the four types of violation of maxim are founded which were the illucutionary function and creating humor are the reasons why speakers flouted those cooporative maxim.